The impact of peer support program on adherence to the treatment regimen in patients with hypertension: A randomized clinical trial study - Ameneh Haidari; Mahin Moeini; Alireza Khosravi (Wolters Kluwer Medknow Publications, 2017)
Background: High blood pressure is the greatest risk factor of death, and patients should manage to control it. Peer support program is used to control chronic diseases. This study aims to determine the effect of peer support program on adherence to the regimen in patients suffering from hypertension. Materials and Methods: This study is a clinical trial conducted among 64 patients with hypertension referring to the Hypertension Research Center (Isfahan. Iran). The information was collected in three stages - before the start of intervention, immediately after, and 1 month after the intervention using a questionnaire of adherence to the treatment regimen for high blood pressure. The questionnaires were filled using a questioning method by patients who were not aware of the study. The experimental group attended 6 sessions of the peer support program (1 hour), and the control group attended two sessions held by the researcher. Data were analyzed using the Statistical Package for the Social Sciences version 18 software, and statistical tests were analyzed using independent t-test and analysis of variance with repeated measures. Results: Before the intervention, there was no significant difference in adherence to the treatment regimen score between the two groups regarding the three aspects of medication regimen, diet, and activity program. Increase in scores of control group immediately after and 1 month after peer support program was higher (p < 0.001) compared to before the intervention. Conclusions: This study showed that peer support programs had a positive impact on adherence to the treatment regimen in patients suffering from hypertension.